HTLV-I associated arthritis: characteristics of an HTLV-I virus infected T cell line from synovial fluid. - Eguchi, K (1992)
A T cell line from mononuclear cells in the synovial fluid of a patient with polyarthritis was established. The T cell line reacted with serum samples positive for antibodies to human T cell lymphotropic virus type I (HTLV-I) and with monoclonal antibody to HTLV-I p19. In Southern blotting with an env-pX-LTR HTLV-I probe and digestion of T cell line DNA with the restriction enzymes ClaI, DraI, and PstI generated fragments that were identical to those found in two HTLV-I infected T cell lines established from adult T cell leukaemia or HTLV-I associated myelopathy. The T cell line expressed CD2, CD3, CD4, CD45RA, CD29, HLA-DR, CD25, and CD26 antigens, but not CD8 and CD20 antigens. Large amounts of interleukin 6, interferon gamma, and tumour necrosis factor alpha were secreted in the culture supernatants of this cell line. This line helped immunoglobulin production by B cells, but not K562, Raji, and synovial cell lysis.